Civilian and Military Genetics: Nondiscrimination Policy in a Post-GINA World - Baruch, Susannah (Elsevier, 2008)
Evidence is emerging of a growing societal consensus about appropriate and inappropriate uses of genetic information. The Genetic Information Nondiscrimination Act of 2008 provides new legal protections to Americans by prohibiting the discriminatory use of genetic information by health insurers and employers. Additionally, the United States military recently created new policies for fair use of genetic information in the determination of benefits for servicemen and servicewomen leaving military service. Although critical issues remain, such as the potential for genetic information to be used to deny people other forms of insurance, and how the military will use genetic medicine overall, significant progress has been made.